Comparative Analysis of common Edge Detection Algorithms using Pre-processing Technique - R. Vijaya Kumar Reddy; K. Prudvi Raju; M. Jogendra Kumar; L. Ravi Kumar; P Ravi Prakash; S. Sai Kumar (Institute of Advanced Engineering and Science, 2017)
Edge detection is the process of segmenting an image by detecting discontinuities in brightness. So far, several standard segmentation methods have been widely used for edge detection. However, due to inherent quality of images, these methods prove ineffective if they are applied without any preprocessing. In this paper, an image preprocessing approach has been adopted in order to get certain parameters that are useful to perform better edge detection with the standard edge detection methods. The proposed preprocessing approach involves median filtering to reduce the noise in image and then Edge Detection technique is carried out. And atlast Standard edge detection methods can be applied to the resultant preprocessing image and its Simulation results are show that our preprocessed approach when used with a standard edge detection method enhances its performance.